Corporate governance mechanisms and risk-taking in South Africa. (6th May 2019) - Singh, Gurcharan; Halari, Anwar; Satoh, William
This study examines the relationship between the quality of corporate governance score and the risk-taking behaviour of firms using data from 120 companies listed on the Johannesburg Stock Exchange (JSE) from 2010 to 2016. More specifically, this study analyses the way in which: 1) compliance to corporate governance; 2) percentage of non-executive directors on the board; 3) total number of board members; 4) percentage of debt; 5) firm size affect risk-taking behaviour in South African firms. Using a dynamic panel data regression model, the research found that corporate governance score and leverage are significant and negatively related with risk. This contradicts prior studies in other markets. Furthermore, the percentage of NEDS, board size and firm size, though positively related, were found to be insignificant risk factors. This can have useful implications for managers in assessing risk behaviour of South African firms.